The Legal Status of Mut’ah Marriage in Indonesia - Mimin mintarsih; Lukman Mahdami (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2021)
Mut'ah marriages with contract marriages bring a dilemma to society. The society views that this is halal (lawful) and legal, but in essence it does not carry out rights and obligations. The problem of this paper is how do civil cases (of mut'ah marriage) get legal certainty so that the logic of